KONTRIBUSI CAREER DECISION MAKING SELF-EFFICACY TERHADAP CAREER INDECISION PADA MAHASISWA TINGKAT AKHIR D-III UNIVERSITAS NEGERI PADANG - Hakim, Arief Rahman; Akbar, Amin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research aims to analyze the contribution of career decision making selfefficacy to career indecision in final year students of the Diploma III (D-III) programat Padang State University. This type of research is a correlational quantitativeresearch with sampling techniques using proportionate stratified random sampling.The population in this research is final year students of D-III State University ofPadang with a sample of 150 respondents. Data collection used the Career decisionmaking self-efficacy (CDMSE) scale and the Career Indecision scale. Data analysisuses classical assumption tests and simple linear regression analysis assisted bythe SPSS program version 20 for Windows. The results of hypothesis testingshowed a significant negative contribution of career decision making self-efficacy tocareer indecision with a significance value of 0.000 (p < 0.05). The value of thedetermination coefficient (R-square) obtained was 0.173, which means that thecareer decision making self-efficacy variable made an effective contribution of17.3% to career indecision, while the remaining 82.7% was explained by otherfactors outside this study model. These results indicate that increasing students'self-confidence in making career decisions can significantly reduce their level ofuncertainty in determining their post-graduation future.